Contemporary Sociological Theory (II) - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2009)
The aim of the article is to identify and critically assess the key concepts, ideas, and the epistemological principles of the contemporary sociological theory. In light of the “peripheral” concerns, the aim of the paper is to identify and critically assess the meta-methodological principles of the contemporary sociological theory. The article focuses on the relations between sociology, society, modernization, and globalization, including the “borderline” Lithuanian case. In the later analysis, the paper focuses on the differences of social theory and sociological theory, the sociological forms and the criteria of their differentiation. The article attempts to provide an understanding of the conceptual connections between social theory and political philosophy. Although the concept of “theory” has deep roots in the professional discourses of East European intellectuals, sociological theory finds itself in a position where it cannot significantly affect the sociopolitical intellectual agenda. Moreover, the theoretical sociology more and more is identified with the role of the ‘under laborer’. The situation is further complicated by the fact that the deterministic scheme of the old (Soviet) historicism corresponds to the optimistic perspective of the new (Western) historicism. The article points out to an urgent need to re-think the perspectives of sociological theory for contemporary times. The article concludes with discussion of criteria in the assessment of status and value of theoretical sociology.
Keywords: sociological theory; social theory; professional sociology; public sociology